2002
DOI: 10.1046/j.0032-0862.2001.656.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi on severity of root rot of bananas caused by Cylindrocladium spathiphylli

Abstract: The interaction between four arbuscular mycorrhizal (AM) fungi, Glomus sp., G. proliferum , G. intraradices and G. versiforme , and the root-rot fungus Cylindrocladium spathiphylli , and subsequent effects on growth and phosphorus nutrition of banana ( Musa acuminata , AAA, cv. Grande Naine) were investigated under glasshouse conditions. Overall, root infection by C. spathiphylli reduced the growth of banana plants, but preinoculation with AM fungi significantly attenuated this detrimental effect. Lower diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 33 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…This suggests the positive benefit of mycorrhizal association during stressed condition than in stress-free condition. Similar kind of observation was made by Declerck et al (2002) on severity in bananas caused by Cylindrocladium spathiphylli. There have been many attributed operative mechanism of pathogen suppression by VAM which may be physical, physiological, biological and in biochemical changes.…”
Section: Total Biomasssupporting
confidence: 53%
“…This suggests the positive benefit of mycorrhizal association during stressed condition than in stress-free condition. Similar kind of observation was made by Declerck et al (2002) on severity in bananas caused by Cylindrocladium spathiphylli. There have been many attributed operative mechanism of pathogen suppression by VAM which may be physical, physiological, biological and in biochemical changes.…”
Section: Total Biomasssupporting
confidence: 53%
“…Piquillo against V. dahliae, the effectiveness of AMF in controlling soil borne pathogens can be affected by several biotic and abiotic factors (Singh et al, 2000). In fact, different Glomus species can exhibit different degree of success as bioprotector agents against a particular pathogen (Habte et al, 1999;Declerck et al, 2002). In a study focused on testing the ability of G. deserticola, G. mosseae and G. intraradices as hypothetical bioprotector agents against Verticillium-induced wilt in pepper, Garmendia et al (2004c) concluded that only G. deserticola was effective to avoid great yield reductions in diseased pepper plants (Fig.…”
Section: Final Considerationsmentioning
confidence: 99%
“…At least under controlled conditions, some varieties of banana exhibit a high mycorrhizal dependency (Declerck et al 1995a). Interactions between AM fungi and Cylindrocladium spathiphylli (Declerck et al 2002) and R. similis (Elsen et al 2001) decrease both the populations of pathogens and disease severity in banana plants. These recent results should be confirmed by field experiments.…”
Section: High-input Cropping Systems In Tropical Areas: Banana Monocumentioning
confidence: 99%